Flexible production, feminisation and disorganisation: evidence from Tirupur Knitwear industry - Neetha, N. (2002)
The paper argues that central to the export success of the Tiruppur industry has been feminisation and the demographic segmentation of the labour force brought about through the disorganisation and reorganisation of production structure and labour process. Young and married women workers constitute about half of the workforce in the industry, concentrated in the lower rungs of production organisation. A direct outcome of the process of feminisation has been its impact on labour relations of the industry, marked by the informalisation of the workers. - Reproduced.
Keywords: Labour